A currency basket and future exchange rate arrangements in Asia. Issue 1 (2nd January 2018) - Shimizu, Junko; Sato, Kiyotaka
Abstract: Due not only to a dominant role of the US dollar in regional trade and financial transactions but also to de facto US dollar pegged exchange rate policy, Asian countries cannot avoid exchange rate risks between their own currency and the US dollar. In recent years, however, the Chinese government has actively promoted the Renminbi (RMB) internationalisation especially in international trade. In December 2015, China introduced a new exchange rate index against a basket of 13 trade-weighted currencies, which can be considered a major turning point from the US dollar standard toward a more flexible currency basket system. However, the estimated implicit basket weights reveal that several Asian economies still tend to stabilise their currencies against the US dollar, while Malaysia and Singapore have stabilised their currencies against RMB in recent years. Since the internationalisation of local currencies and regional monetary arrangements are typically facilitated with each other, further progress of RMB internationalisation is expected to promote a leading role of China in establishing regional exchange rate policy coordination.